Pengaruh Penggunaan KB Suntik Depo Medroksiprogesteron Asetat (DMPA) Terhadap Kenaikan Berat Badan Di Praktek Mandiri Bidan Dwi Ekowati, Kulon Progo, Yogyakarta - Eva Putriningrum; Fatimah Dewi Anggraeni (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2021)
Introduction: Family planning is one of the government strategies in solving population problems and prevent maternal mortality and morbidity. Progestin injections contraceptives method is very effective, easy, practical, and inexpensive for women. However, progestin-injected contraceptives can also cause various side effects, such as weight gain, menstrual disorders, and a slower return of fertility. Objectives: The purpose of this study was to analyze whether there was an effect of using DMPA injection contraceptive on weight gain (BB) in PMB Dwi Ekowati, Kulon Progo, Yogyakarta. Methods: The research method used a pre-experimental design. The sample of this study were 20 mothers who used progestin injection contraception. The sample technique used purposive sampling, and the analysis used Paired t-test. Results: The results of this study indicate that the body weight of the acceptors before using DMPA injection contraceptive was 52.3 kg and after using contraception was 56.7 kg. The average weight gain in the first year is 0.6 kg, the second year is 3.5 kg, and the third year is 4.4 kg. There is an effect of using DMPA contraceptive method in increasing the body weight in the second and third years (p value 0.001 and 0.000), while there is no effect in the first year (p value 0.515).